The Crisis in Latin America : strategic, economic, and political dimensions - Falcoff, Mark.; Grunwald, Joseph; Wiarda, Howard J.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1984)
The papers presented here grew out of the AEI's December 1982 Public Policy Week forum on "The Crisis in Latin America".
Based on papers presented at AEI's Dec. 1982 public policy week forum.
Includes bibliographical references.
osc 30/01/2019
Loans
Keywords: Politica and government; Economic history; Latin America; United States